Analisis Kemapuan Penyelesaian Soal Matematika Berorientasi Pisa dalam Konten Perubahan dan Hubungan pada Siswa SMP - Sutama, S.; Sofia, S.; Novitasari, M. (Jurnal VARIDIKA, 2019)
This research aims to describes the process of problem solving question of PISA in students. This research use a qualitative of research methods. The subject of this research grade VIII A SMP Negeri 1 Teras amounted to 28 students. Data collection techniques are used tests, interviews, and documentation method. In this research the validity of data using triangulation techniques to compare test results data, interviews, and documentation. Quantitative data analysis techniques using whereas reduction, serving until the conclusion of the withdrawal measures adapted to the Polya. The results of this research were obtained conclusions high-capable Students can meet all the indicators in the settlement of the question of maximum, medium and low skilled students not consistent in performing the stages of completion of a matter so that insufficient.